Racial Inequality in the Twenty-first Century: A Comparative Analysis between Brazil and the United States. (June 2022) - Freitas, Antonio; Miebach, Alessandro
This article presents a set of comparative data related to racial inequality in the United States and Brazil throughout the twenty-first century. Within the limitations of available data, we highlight four limited but important dimensions, that is, demography, education, the labor market, and earnings that illustrate racial inequality in both countries. In doing so, we aim to investigate and critically update Andrews's work (1992) on the last three decades with available data. Despite some improvements in absolute terms related to racial inequities, we show that in both Brazil and the United States, economic growth periods do not necessarily mean that income among blacks is catching up with that of whites. Similarly, in both countries, economic crisis and recovery phases are experienced differently depending on the individual's race. JEL Classification: D31, D63, J7, J15